Eyes on communication: trialling eye-gaze control technology in young children with dyskinetic cerebral palsy. (17th February 2019) - Karlsson, Petra; Bech, Anna; Stone, Helen; Vale, Cecily; Griffin, Suzan; Monbaliu, Elegast; Wallen, Margaret
ABSTRACT: Purpose : This study aims to identify eye-gaze control technology outcomes, parent perception of the technology and support received, and gauge the feasibility of available measures. Methods : Five children with dyskinetic cerebral palsy, mean age 4 years, 4 months (1 year, 0 months); n  = 4 males; trialled two eye-gaze control technology systems, each for six weeks. Parents completed pre- and post-questionnaires. Results : Parents found the 6-week home-based trial period to be the right length. Written guidelines and instructions about set-up, calibration, and play and learning activities were perceived as important. Children demonstrated improvements in goal achievement and performance. Parents found questionnaires on quality of life, participation, behaviours involved in mastering a skill and communication outcomes challenging to complete resulting in substantial missing data. Conclusion : Eye-gaze control technology warrants further investigation for young children with dyskinetic cerebral palsy in a large international study.